2022
DOI: 10.3390/cancers14153603
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Endoscopic Submucosal Dissection and Surgery in Patients with Early Gastric Cancer

Abstract: Background: Endoscopic submucosal dissection (ESD) has become a preferred treatment option for early gastric cancer (EGC). This study aimed to compare the clinical outcomes of ESD and surgical resection for EGC. Methods: This was a retrospective case–control study. Patients with a diagnosis of EGC who underwent ESD or surgery in our hospital from 2011 to 2020 were enrolled. We compared the clinical characteristics and treatment outcomes of these two groups according to propensity score-matching. The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The results overlap with those stated above for general cohorts, with ESD showing a significantly lower 5-year DFS, no statistical difference in DSS, and similar OS (Table 4). A number of studies have reported on the hospital costs associated with either procedure [69][70][71]. ESD seems to account for significantly lower costs when compared to surgery, which is mostly due to the nature of the procedure itself and differences in the length of stay.…”
Section: Endoscopic Resection Versus Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…The results overlap with those stated above for general cohorts, with ESD showing a significantly lower 5-year DFS, no statistical difference in DSS, and similar OS (Table 4). A number of studies have reported on the hospital costs associated with either procedure [69][70][71]. ESD seems to account for significantly lower costs when compared to surgery, which is mostly due to the nature of the procedure itself and differences in the length of stay.…”
Section: Endoscopic Resection Versus Surgerymentioning
confidence: 99%
“…A number of studies have reported on the hospital costs associated with either procedure [ 69 , 70 , 71 ]. ESD seems to account for significantly lower costs when compared to surgery, which is mostly due to the nature of the procedure itself and differences in the length of stay.…”
Section: Endoscopic Resection Versus Surgerymentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) is considered the first-line treatment for EGC regardless of its size or ulceration[ 4 ]. When compared to gastrectomy, ESD provides faster recovery, lower costs, and superior quality of life for patients with EGC.…”
Section: Introductionmentioning
confidence: 99%